Branding patriarchy: The rituals and design choices of the all-male Greek-Cypriot coffee shop - Papadima, Aspasia (My University, 2019)
Patriarchy is a social construct (Lerner, 1986; Miller, 2015) that conceals social hierarchy, conservative ideology, stereotypes and discrimination (Pratto, 1999; Sidanius & Pratto, 1999). The emergence of patriarchy, as part of the evolution of human society, has been studied based on theories and evidence that draw material from archeology, history, biology, anthropology, psychology, as well as cultural and ethnographic research. The origins of patriarchy, closely related to the rise of social injustice, are based on the masculine physical strength and genetic strategies to assure reproduction, the strategics of human organization as well as cultural conditions that allowed and reinforced such beliefs. Orthodox Christianity, a fundamental and highly valued institution within Greek-Cypriot society, has been always supporting and promoting patriarchy. The traditional Cypriot coffee-shop, a purely male-ruled public space, echoes the notions attributed to patriarchy, as predetermined social interaction promotes the hegemonic male identity and produces gender difference by “doing gender” (Cătălina-Ionela, 2015; Connell, 2005; West & Zimmerman, 1987). Thus, Bourdieu’s (2001) masculine domination is clearly manifested in the Cypriot coffee-shop, the public place reserved for men –who are entitled in leisure time– as opposing to home, the private space reserved for women that lack their own free time. This study examines through empirical research, based on both primary and secondary data, how patriarchy is demonstrated, promoted and preserved –in other words, branded- within the Cypriot coffee-shop culture. “Gender performance” is being observed in language, folk literature, everyday practices and space, and as such, including the spatial and visual infrastructure of traditional Cypriot coffee-shops allows us to derive into corresponding and relevant conclusions with the aid of different methodological tools such as semiotic analysis, focus groups and photo elicitation.
Keywords: patriarchy, masculinity, traditional coffee-shop, doing gender, male public space, Cypriot culture, typography, coffee-shop signs